Ultrasound diagnostics of the intestinal trauma - O. A. Alekseechkina; E. Ya. Dubrov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of the Study. The elaboration of the diagnostics of the intestinal and mesenterial injuries in the closed abdominal trauma.Materials and methods. On the basis of the analysis of more than 6500 examinations of the patients with closed abdominal trauma 49 cases were discovered: the rupture of intestinal mesentery with bleeding (22 cases), mesentery hematoma (12 cases), the peritonitis due to the intestinal injury (8 cases), the hematoma of the intestinal wall (7 cases).Results. The patients were divided into the three groups: the1st group (22 cases) – the discovery of the trauma signs in the first hours after the trauma, the 2nd group (10 cases) – the trauma was discovered during the first two days, the 3d group (17 cases) – in the process of the clinical observation.Conclusions. The diagnostics of the intestinal and mesenterial injuries in the closed abdominal trauma is based on the combination of the ultrasound signs – the free liquid in the abdominal space, the mass (hematoma) in the intestinal mesentery, the local thickening of the intestinal wall with the minimal quantity of the free liquid inter loops, the peritonitis signs.